Coulomb breakup reactions of 93, 94Zr in inverse kinematics. (28th January 2019) - Takeuchi, Satoshi; Nakamura, Takashi; Shikata, Mizuki; Togano, Yasuhiro; Kondo, Yosuke; Tsubota, Junichi; Ozaki, Tomoyuki; Saito, Atsumi; Otsu, Hideaki; Wang, He; Sakurai, Hiroyoshi; Watanabe, Yukinobu; et al.
Abstract: Coulomb breakup reactions of ^93, 94 Zr have been studied in inverse kinematics at incident beam energies of about 200 MeV/nucleon in order to evaluate neutron capture reaction methods. The ^93 Zr(n, γ )^94 Zr reaction is particularly important as a candidate nuclear transmutation reaction for the long-lived fission product ^93 Zr in nuclear power plants. One- and two-neutron removal cross sections on Pb and C targets were measured to deduce the inclusive Coulomb breakup cross sections, 375 ± 29 (stat.) ± 30 (syst.) and 403 ± 26 (stat.) ± 31 (syst.) mb for ^93 Zr and ^94 Zr, respectively. The results are compared with estimates using the standard Lorentzian model and microscopic calculations. The results reveal a possible contribution of the pygmy dipole resonance or giant quadrupole resonance in the Coulomb breakup reactions of ^94 Zr.